Depresión durante el embarazo y su relación con la Violencia familiar en adolescentes atendidas en el Hospital Minsa II – 2 Tarapoto, Julio – Diciembre 2015 - Lozano Tasayco, Cinthia Pamela (2015)
This research paper entitled "Depression during pregnancy and its relation to family Violence in adolescents treated at MINSA Hospital II - 2 Tarapoto, July-December 2015", quantitative, descriptive, correlational, cross, applied, whose sample was 100 Pregnant adolescents, was used as a methodology and an instrument interview Questionnaire containing questions to determine the variables violence and Depression. Among the results we have pregnant teenagers are characterized by: 65.8% (79) is Aged between 15-17 years of high school degree 77.5% (93), single marital status 50.0% (60) come from Tarapoto 35.5% (43) of Catholic 80.8% (97). Among the types Of violence that pregnant teenagers are presented: psychological 79.2% (95) 67.5% Economic violence (81), physical violence 62.5% (75) and sexual violence 40.8% (49), predominantly psychological violence. 37.5% of pregnant adolescents have an Average degree of depression. Physical violence, followed by piscolgica violence are The most related to the degree of depression in pregnant teenagers. In conclusion there is significant relationship at 5% (if p <0.05) between the types of Violence and the degree of depression, so the research hypothesis is accepted